2015
DOI: 10.1109/les.2015.2477273
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening SIMON Implementation Against Intelligent Fault Attacks

Abstract: Driven by malicious intent, attackers are impelled to extract the cipher key and thus compromise the cryptosystem through fault attacks. Existing fault-detection methods can effectively detect random faults in the cipher implementation, but yield a high fault bypass rate (FBR) under intelligent fault attacks. To address this limitation, we propose a new microarchitecture to thwart fault attacks that place mathematically symmetric faults on the two encryption data paths. To further reduce the FBR for a new ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Theorem 2 Consider system (7), and the reconstruction algorithm (20)- (22). Define the reconstruction error e σi(k) (k) := ûσi(k) (k) − u i−1 (k), and let Assumption 1 be satisfied; then,…”
Section: A Reconstruction Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 2 Consider system (7), and the reconstruction algorithm (20)- (22). Define the reconstruction error e σi(k) (k) := ûσi(k) (k) − u i−1 (k), and let Assumption 1 be satisfied; then,…”
Section: A Reconstruction Strategymentioning
confidence: 99%
“…We let step k, let one of the 3 communication channels between the two vehicles be randomly selected to be attacked, i.e., W 2 (k) = {1}, {2} or {3} and let η W2(k) ∼ N (0, 5 2 ). For all k ≥ 0, the second vehicle uses ( 20)- (22) to construct an estimate û1 (k) of u 1 (k). The performance of the fusion algorithm is shown in Figure 2.…”
Section: A Reconstruction Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Several protection schemes are evaluated in [52] which showed that many of them do not perform better than straightforward solutions like hardware duplication or repetition of code. The work of [53] proposes a new microarchitecture to handle faults bypassing double modular redundancy structures. In [54] a framework for identification of vulnerabilities in a crypto implementation based VOLUME 11, 2023 on known vulnerable operations in the cipher is presented.…”
Section: Related Workmentioning
confidence: 99%
“…Boneh proposed fault attack to access the key of RSA and CRT algorithm [23]. This attack method can be used in different cipher algorithms, such as DES, AES, PRESENT and SIMON and corresponding anti-fault attack method has been proposed [4,24,25,26]. Debdeep and Michael implement a fault attack on AES-128 by inject error bits on the eighth round, and proposed the hack equations about ninth and tenth rounds injection [27,28].…”
Section: Introductionmentioning
confidence: 99%